Follow-up campaign of the Blazhko star RR Lyr - Kolenberg, K.; Ulus, N. D.; Beck, P. G.; Gazeas, K. D.; Tsantillas, S.; Robertson, C. W. (Communications in Asteroseismology, 2008)
Stars with changing Blazhko periods challenge the currently proposed hypotheses for the Blazhko effect. RR Lyr, the prototype of the class, is one of the best-studied Blazhko stars but it keeps on surprising its observers. We present the first results from a photometric follow- up campaign in 2006-2007 of the star. Multicolour data were gathered from 4 different observatories in the northern hemisphere. Our analysis focuses specifically on the period behaviour. We confirm the previously reported decrease of the modulation period.